Iridium‐Catalyzed Formyl‐Selective Deuteration of Aldehydes - Kerr, William J.; Reid, Marc; Tuttle, Tell (Angewandte Chemie International Edition, 2017)
We report the first direct catalytic method for formyl‐selective deuterium labeling of aromatic aldehydes under mild conditions, using an iridium‐based catalyst designed to favor formyl over aromatic C−H activation. A good range of aromatic aldehydes is selectively labeled, and a one‐pot labeling/olefination method is also described. Computational studies support kinetic product control over competing aromatic labeling and decarbonylation pathways. Al(D)hydes: An iridium catalyst system was designed to effect formyl over aryl C−H activation of aromatic aldehydes. Computational studies support kinetic product control over competing aromatic labeling and decarbonylation pathways.